2017
DOI: 10.1093/eurheartj/ehw582
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-dependent trimethylamine N-oxide in acute coronary syndromes: a prognostic marker for incident cardiovascular events beyond traditional risk factors

Abstract: Plasma TMAO levels among patients presenting with chest pain predict both near- and long-term risks of incident cardiovascular events, and may thus provide clinical utility in risk stratification among subjects presenting with suspected ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
313
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(334 citation statements)
references
References 49 publications
(94 reference statements)
7
313
1
3
Order By: Relevance
“…They have also shown that plasma TMAO concentrations can predict an enhanced risk of major adverse cardiac events in two independent cohorts 76) .…”
Section: Short Chain Fatty Acids and Atherosclerosismentioning
confidence: 96%
“…They have also shown that plasma TMAO concentrations can predict an enhanced risk of major adverse cardiac events in two independent cohorts 76) .…”
Section: Short Chain Fatty Acids and Atherosclerosismentioning
confidence: 96%
“…For example, elevated TMAO levels are strongly correlated with increased risk of adverse cardiovascular outcomes, including heart attack, stroke and death risk (Tang and Hazen, 2014, 2017; Tang et al, 2015; Kitai et al, 2016; Li et al, 2017). Elevated TMAO levels also exacerbate pressure overload-induced heart failure (Organ et al, 2016) and prolong hypertensive effect of angiotensin II (Ufnal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TMAO stems from microbial conversion of dietary nutrients containing choline, phosphatidylcholine, and L‐carnitine to trimethylamine, which is absorbed by the intestinal tube and converted to TMAO by a hepatic flavin monooxygenase 3 4. Studies in animals have demonstrated that TMAO possesses proatherogenic property, and clinical studies have demonstrated that circulating levels of TMAO independently predicted cardiovascular events such as myocardial infarction and cardiovascular death 5. More recent studies have also documented that TMAO possesses prothrombotic effect by activating human platelets via increased release of Ca 2+ from intracellular stores 6…”
Section: Introductionmentioning
confidence: 99%